A novel, topical, nonsteroidal, TRPV1 antagonist, PAC-14028 cream improves skin barrier function and exerts anti-inflammatory action through modulating epidermal differentiation markers and suppressing Th2 cytokines in atopic dermatitis. Issue 2 (August 2018) - Lee, Ji-Hae; Choi, Chang Soon; Bae, Il-Hong; Choi, Jin Kyu; Park, Young-Ho; Park, Miyoung
Highlights: PAC-14028 1% topical cream is an anti-inflammatory, non-steroidal TRPV1 antagonist. PAC-14028 cream treatment reduced AD-like symptoms and improved skin barrier functions in Ox-induced in vivo murine model. PAC-14028 suppressed the signaling pathways including IL-4/-13 mediated activation of JAK/STAT, TRPV1, and neuropeptides. Abstract: Background: Although it is established that epidermal barrier disturbance and immune dysfunction resulting in IgE sensitization are critical factors in the development of cutaneous inflammation, the pathogenesis and targeted therapy of atopic dermatitis (AD)-specific pathways have still been unknown. Objective: Taking into account the fact that Th2 cytokines in AD have both unique and overlapping functions including increased epidermal thickening, inflammation, and decreased expressing of the barrier proteins keratinocyte differentiation, we sought to clarify our hypothesis that TRPV1 antagonist plays a critical role in skin barrier function and can be a therapeutic target for AD. Methods: AD-like dermatitis was induced in hairless mice by repeated oxazolone (Ox) challenges to hairless mice. The functional studies concerning skin barrier function, anti-inflammatory action, and molecular mechanism by TRPV1 antagonism were conducted by histopathological assays, ELISA, qPCR, western blotting, and skin blood flow measurement. Results: Topically administered TRPV1 antagonist, PAC-14028 (Asivatrep: C21 H22 F5 N3 O3 S), improved AD-like dermatitis and skin barrier functions, and restored the expression of epidermal differentiation markers. In addition, the PAC-14028 cream significantly inhibited cutaneous inflammation by decreasing the expression of serum IgE, and the epidermal expression of IL-4, and IL-13 in Ox-AD mice. These results may provide a novel insight into the molecular mechanism of PAC-14028 cream involved in anti-inflammatory effects and skin barrier functions by suppressing the multiple signaling pathways including IL-4/-13-mediated activation of JAK/STAT, TRPV1, and neuropeptides. Conclusion: PAC-14028 cream can be a potential therapeutic tool for the treatment of chronic inflammation and disrupted barrier function in patients with AD.